Treatment of Type 2 Diabetes 2015
DOI: 10.5772/59119
|View full text |Cite
|
Sign up to set email alerts
|

Can Adiponectin be a biomarker for Ethnic heterogeneity in Diabetes Mellitus?

Abstract: The authors declare that there is no conflict of interest that could be perceived as prejudicing the impartiality of the research reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…However, such diagnostic tests should be highly specific and sensitive. [9,71] Hence, the overall primary requirements and benefits of NBS program are summarized in Figure 2. Moreover, overall usage of each technique in NBS, advantages, and disadvantages [57] are listed in Table 2 with more detail.…”
Section: Requirements and Benefits To Establish A Nbs Programmentioning
confidence: 99%
“…However, such diagnostic tests should be highly specific and sensitive. [9,71] Hence, the overall primary requirements and benefits of NBS program are summarized in Figure 2. Moreover, overall usage of each technique in NBS, advantages, and disadvantages [57] are listed in Table 2 with more detail.…”
Section: Requirements and Benefits To Establish A Nbs Programmentioning
confidence: 99%
“…As an example, Figure 7a shows a waveguide (panel i) fabricated using a combination of bottom-up/top-down processes; the device is strain tuned and was demonstrated when integrated with a quantum emitter and a planar integrated optical resonator consisting of a silicon nitride ring resonator fabricated on a piezoelectric substrate (panel ii). The tunability of the devices was tested by applying a voltage to the piezoelectric substrate while the quantum dot emission collected through the waveguide was recorded with the focusing optical fiber (panel iii) [137,138] . Ideally, an adiabatic coupling between the plasmon polaritons into a dielectric waveguide enables an efficient collection and simultaneously a significant enhancement of the sensitivity; the two conditions have been implemented in the photonic cavity like a whispering gallery mode that integers plasmonic structures in an opportune architecture for achieving the enhancement [139] [140] .…”
Section: Quantum Plasmonic Microsystem Biosensorsmentioning
confidence: 99%
“…Jung et al [25] reported a significant relationship between ALR and the presence of MetS and the number of metabolic components in the population. A recent study also established that the ALR was a better marker for the assessment of acute metabolic stress [26]. LAR was served as a sensitive marker for the early detection of MetS [27,28].…”
Section: Introductionmentioning
confidence: 96%